Sorghum (Sorghum bicolor L. Moench var. bioguma) Cookies (SoKis): Source of Antioxidant and Prebiotic - Wiryawan, Dwiki Maycellino; Ariestanti, Catarina Aprilia; Prasetyaningsih, Aniek (agriTECH, 2024)
Sorghum bicolor L. Moench,  locally called “cantel,” is an underused local food in Indonesia, which contains resistant starch and has the potential to act as prebiotic. Several studies have also reported the role of its phytochemical compounds as antioxidants. Therefore, this study aims to determine the potential of sorghum as a source of antioxidants and prebiotic in cookies products. Sorghum was dried under various temperatures (40, 55, and 70 °C) for 4 h, ground into flour, and used in cookies production to replace wheat flour (WF) in various ratios of sorghum flour (SF):WF (0:100, 25:75, 50:50, 75:25, 100:0 % (w/w)). Phytochemical compounds were tested using the maceration method and qualitatively by assessing the color change and physical appearance of SF. Antioxidants activity was analyzed using the 1,1-diphenyl-2- picrylhydrazyl (DPPH) method, while nutritional content was determined with proximate analyses. The total plate count (TPC) method was carried out to assess the growth of Bifidobacterium longum, and organoleptic test (n = 30) was performed using 5 points-hedonic scale. SF with a drying temperature of 55˚C was used as an ingredient for making cookies based on its moisture content (4.24 ± 0.084) and antioxidant activity value (70.77 ± 2.91%). The analysis results showed the presence of flavonoid, alkaloid, tannin, and polyphenol compounds in SF. Cookies with SF:WF ration of 50:50 (w/w) (SoKis) showed the best acceptance based on organoleptic test compared to the other formulation with antioxidant activity of 36.18 ± 2.56%. In addition, soKis contained 2.715% water, 1.425% ash, 24.57% fat, 8.24% protein, 63.05% carbohydrate, 0.255% crude fiber and could support the growth of B. longum with a value of 2.46 × 10 8 CFU/mL. Based on these results, sorghum could be used and developed as a functional food ingredient.